Implications of high-resolution velocity and strain rate observations for modelling of Greenlandic tidewater glaciers - Dominik Fahrner; Pablo J. González; Douglas W. F. Mair; James M. Lea (Journal of Glaciology)
Synthetic Aperture Radar (SAR) has been used extensively to determine the surface ice flow velocity of tidewater glaciers and investigate changes in seasonal or annual ice dynamics at medium spatial resolution (⩾100 m). However, assessing tidewater glacier behaviour at these resolutions risks missing key details of glacier dynamics, which is particularly important for determination of strain rates that relate to crevasse formation, depth, and ice damage. Here we present surface ice velocity and strain maps with a 16 m posting derived from high-resolution (1 m) PAZ Ciencia spotlight mode SAR imagery for Narsap Sermia, SW Greenland, for October 2019 to February 2021. Results reveal fine details in strain rate, including an area of compression proximal to the terminus, with an upstream shift of strains through time. The velocity evolution of Narsap Sermia shows distinct seasonal changes starting in summer 2020, which are largely modulated by the subglacial drainage system. Comparison of our results with medium-resolution velocity products shows that while these can capture general strain and velocity patterns, our high-resolution data reveals considerably larger ranges of strain values. This is likely to have implications for tuning strain rate dependent calving and ice damage parameterisations within numerical models.